The Role of Coronary Artery Calcium Score as a Systemic Marker of Atherosclerosis: A Cross-sectional Imaging Study - Mohammad Sidqi Aulia; Raymond Pranata; Syarief Hidayat; Nuraini Yasmin Kusumawardhani (The Indonesian Heart Association, 2026)
Following publication of this article, the authors notified the Editorial Office of an error in the order of authorship. The order of the author is wrong and should have been:Mohammad Sidqi Aulia, Raymond Pranata, Syarief Hidayat, Nuraini Yasmin KusumawardhaniAll authors have provided written consent to approve the revised authorship order. The authorship order has now been corrected in the published article. The authors apologize for any inconvenience caused by this error.